Hexokinase Domain Containing 1 (HKDC1) Gene Variants and Their Association With Gestational Diabetes Mellitus: A Mini-Review - Sekar Kanthimathi; Polina Popova; Viswanathan Mohan; Wesley Hannah; Ranjit Mohan Anjana; Venkatesan Radha (Journal of Diabetology)
Gestational diabetes mellitus (GDM) is the most common metabolic disorder during the gestational period. Maternal glucose metabolism differs significantly from nonpregnant levels during pregnancy, with increased insulin resistance being the main physiological response. Maternal glucose levels during pregnancy, have a significant impact on the development of early and long-term metabolic health of the offspring. Therefore, a better understanding of the GDM pathophysiology is needed. Hexokinase domain containing 1 (HKDC1) gene was discovered as a gene related to glucose metabolism during pregnancy compared with nongravid state. HKDC1 plays a critical role in glucose homeostasis during pregnancy. Haplotypes of HKDC1 genetic variants associated with 2-h plasma glucose (2hPG) in pregnancy, disrupt regulatory element activity, thereby reducing HKDC1 expression in different tissues. The association of HKDC1 variants with gestational diabetes and 2hPG was investigated in several ethnic groups. These studies suggested that HKDC1 plays a more important role in glucose metabolism during pregnancy than outside of it and also demonstrated that while GDM and type 2 diabetes mellitus have many similarities, there are differences in at least one underlying pathway. This review focuses on the findings of the genetic studies on HKDC1 and GDM.